Process of analysis and design of income accounting information system (case study of PT. MARCI) - Rizki Ahmad Fauzi; Darwin Marasi Purba (STIE Binaniaga, 2021)
Abstract: To increase the competitiveness of a company requires information, including accounting information. With a good accounting information system, it is hoped that the results of physical process efficiency, data updates and accuracy will be achieved. The system design methodology in making the system goes through the stages (1) System Survey (2) System Analysis (3) System Design (4) System Development (5) Testing (6) System Implementation (7) System maintenance. However, with limited time and funds, the researcher completed the research to the system design stage in the form of standard operating procedures (SOP). As for the conclusion, it was found that the work was still inconsistent (same work but implemented in different ways), recording errors, process delays and poor quality.The system design model that has been prepared by the researcher for the Income Accounting Information System of PT Marci consists of the following procedures: (1) order receipt (2) contract agreement (3) work process (4) billing (5) recording. Keywords: System design, accounting information system, PT MARCI